World heritage as authentic fake: Paradisic Reef and Wild Tasmania. (17th November 2022) - Pocock, Celmara; Collett, David; Knowles, Joan
Abstract: This paper explores how the imagined landscapes that act as a catalyst for World Heritage listing, are unable to be reconciled with formal heritage assessments. We explore this tension through two Australian World Heritage landscapes: the Great Barrier Reef and the Tasmanian Wilderness. The history of these listings suggests a teleological process driven by a desire to create authentic utopias. While utopias are imagined spaces, Paradise at the Reef and the Tasmanian Wilderness are realised through hyperreal landscapes (fakes). However, these wholistic landscapes dissolve into a series of inventories of species and numbers in official listing. We suggest the failure to recognise the hyperreal is a form of false consciousness that creates a tension between managing for formally recognised values and managing the unmanageable utopia, and that a broader use of cultural landscapes might be useful in addressing this divide.